Emergence of long-range angular correlations in low-multiplicity proton-proton collisions - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Kroesen, Martin; et al. (Physical review letters, 2024)
This Letter presents the measurement of near-side associated per-trigger yields, denoted ridge yields, from the analysis of angular correlations of charged hadrons in proton-proton collisions at √𝑠=13 TeV. Long-range ridge yields are extracted for pairs of charged particles with a pseudorapidity difference of 1.4<|Δ⁢𝜂|<1.8 and a transverse momentum of 1<𝑝T<2 GeV/𝑐, as a function of the charged-particle multiplicity measured at midrapidity. This Letter extends the measurements of the ridge yield to the low multiplicity region, where in hadronic collisions it is typically conjectured that a strongly interacting medium is unlikely to be formed. The precision of the new low multiplicity results allows for the first direct quantitative comparison with the results obtained in e+⁢e− collisions at √𝑠 =91 GeV and √𝑠=183-209 GeV, where initial-state effects such as preequilibrium dynamics and collision geometry are not expected to play a role. In the multiplicity range 8 ≲⟨𝑁ch⟩ ≲24 where the e+⁢e− results have good precision, the measured ridge yields in 𝑝⁢𝑝 collisions are substantially larger than the limits set in e+⁢e− annihilations. Consequently, the findings presented in this Letter suggest that the processes involved in e+⁢e− annihilations do not contribute significantly to the emergence of long-range correlations in 𝑝⁢𝑝 collisions.